Bovine β-Casomorphins: Friends or Foes? A comprehensive assessment of evidence from in vitro and ex vivo studies. (October 2021) - Daniloski, Davor; McCarthy, Noel A.; Vasiljevic, Todor
Abstract: Background: Complex polymorphisms in the polypeptide chain of bovine β-casein are responsible for the genetic variants that give rise to different bioactive peptides during in vitro and ex vivo digestion, or food fermentation. One specific group of bioactive peptides, known as β-casomorphins, are opioid-agonists for μ-receptors and have been suggested to assume an active role in the development of various non-communicable diseases, including diabetes mellitus, cardiovascular diseases, neurological disorders, pulmonary inflammation, to name a few. Their potential bioactivity and role in human health is dependent on their release from the latent form within the primary structure of β-casein, which can occur during the manufacture of dairy products or during gastric and intestinal digestion. Consequently, β-casomorphins can be either completely hydrolysed or absorbed in the gut or be transferred into the blood stream and internal organs in their intact form. Their biological function as opioid agonists is expressed in the gut, thus upon epithelial translocation they may affect various physiological states, such as causing gastrointestinal issues, bloating, and lactose intolerance. Scope and approach: This review evaluated the possible disadvantages and potential beneficial effects of β-casomorphins on human health, within the scope of in vitro and ex vivo studies. Applying a systematic approach, a literature search was performed across four electronic databases (Scopus, Web of Science, PubMed, and Cochrane) to identify suitable studies. Key findings and conclusions: The data mined from in vitro and ex vivo trials on the health impact of β-casomorphins is both inconclusive and limited to completely support the possible adverse or potential beneficial health effects of β-casomorphins. These peptides are usually further cleaved in the gut, which prevents their migration across the gut-blood-brain barrier. Nevertheless, in some individuals that are immunocompromised, their condition increases permeability of the gut barrier often referred to as a "leaky gut" condition. Thus, the absorption of β-casomorphins appears possible. This may indicate that the presence of β-casomorphins can affect gastrointestinal functions only. However, since the overall concern with β-casomorphins appears debatable and not well defined, more experimental trials are required to investigate the metabolic pathways of these identified peptides, their release during digestion, and subsequent fate after the digestion process. Consequently, repeatability of the findings under a number of other laboratory conditions is required before the data can be fully substantiated. Due to the rapidly evolving nature of the issue and emerging studies in this field, further exploration into the bioactivity of β-casomorphins is warranted. Graphical abstract: Image 1 Highlights: Identification and potential effects of bovine β-casomorphins on human and animal organisms were systematically analysed. Bovine β-casomorphins may possess potential beneficial and possible negative implications for human and animal health. Bovine β-casomorphins may be transported into the human blood only if the permeability of the gut barrier is compromised. Serum enzymes may degrade and eliminate bovine β-casomorphins from the blood stream, before accessing the internal organs.